Allogeneic hematopoietic stem cell transplantation could improve survival for pure CBF-AML patients with minimal residual disease positive after the second consolidation. Issue 4 (21st March 2021) - Wang, Tanzhen; Zhou, Biqi; Zhang, Jubin; Zhang, Xinyue; Liu, Tianhui; Qiu, Huiying; Sun, Aining; Chen, Suning; Wu, Depei; Xu, Yang
Abstract: The role of MRD-directed risk stratification strategy for core binding factor acute myeloid leukemia (CBF-AML) patients with favorable risk genetics is still unknown. We retrospectively analyzed the clinical outcomes of 148 pure CBF-AML patients with first complete remission including MRD positive ( n = 69) and MRD negative ( n = 79) after two courses of consolidation from January 2009 to December 2018 in our center. We found that MRD positive after 2 courses of consolidation significantly influenced OS (5-year: 59%), PFS (5-year: 36%) and CIR (5-year: 58%) in favorable-risk CBF-AML patients with CR1. It was worth noting that the MRD status after two courses of consolidation might be the best timing for treatment choice and allo-HSCT was a promising treatment for favorable-risk CBF-AML patients with MRD positive after the second consolidation.